THE EFFECT OF KNOWLEDGE MANAGEMENT AND ORGANIZATIONAL INNOVATION ON IMPROVING THE LEVEL OF ORGANIZATIONAL AGILITY OF MEGAMOTOR COMPANY - Sahar, Soheila Shame (IJRDO - Journal of Business Management, 2022)
The aim of the present study is to investigate the effect of knowledge management and organizational innovation on Megamotor Company’s agility. In order to find out whether there is a relationship between these two variables, a filed research was selected. The time frame of the present study is from February 2017 to July 2018 and the time of distribution of the questionnaire was May 2018. The present study is a part of the field of management and in relation to the effectiveness of the mediating role of innovation and knowledge management on company’s agility. 335 people were randomly selected as the ultimate subjects of the present study. Analyzing the obtained data, it was found that there is a meaningful relationship between knowledge management and organizational innovation.